New reports of Daldinia species from Kolhapur and Raigad Districts (M.S.), India - Patil, Ketaki; Patil, Anjali; Patil, Mansaram (International Journal of Biological Research, 2016)
Genus Daldinia Ces. & De Not. Belongs to family Xylariaceae. Present paper describes ten species of Daldinia viz. D. â€œbakeriâ€ taxon B sensu Dennis, D. concentrica (Bolton) Ces. & De Not., D. cupra Starback, D. dennissii var. microspora Wollw. & M. Stadler, D. Â  Â  Â pal-mensis M. Stadler, Wollw. &Tichy, D. petriniae Y. M. Ju, J. D.Rogers and F. San Martin, D. raimundi M. Stadler, Venturella &Wollw., D. theissenii Laessoe, J. Fourn. & M. Stadler, D. bakeri Lloyd, D. loculata (Lev.) Sacc. Collected from Kolhapur and Raigad Districts of Maharashtra State, India.